RANCANG BANGUN DAN PENGUJIAN ALAT TANAM MURBEI - Radite Praeko Agus Setiawan; Wawan Hermawan; Lenny Saulia; Syahrial Sabaniah (Jurnal Agritechno, 2022)
Mulberry (Morus Sp.) is widely used in sericulture as silkworms’ fodder. Aside from being a silkworm feed, mulberry plants can also be used as food crops, animal feed and medicine. Mulberry plant breeding can be done by two methods, generative method (through seeds) and vegetative method (part of the plant itself). Vegetative seedlings methods have been done by many silk farmers. Vegetative techniques are relatively easier to do and quickly get leaf production. Vegetative techniques that are mostly used is stake. In mulberry cultivation, one of the processes that consumes a lot of energy is the planting process. Planting mulberry stake is still done manually. In this study planter will be designed which are expected to increase the capacity and efficiency of planting. The design process includes a preliminary study in the form of a study of material characteristics to determine design criteria. After that, the selection of components and mechanisms is carried out, followed by making drawings and prototypes. Planter prototypes tested with static test to evaluate the function of metering device. The Result obtained collecting function error is 0.5 % with one case where metering device fail to collect and zero case of more than one stake collected. The average of damaged stake is 2 % but mostly happen in left metering device with 4 %. The number indicates that modification is needed.